AKUNTANSI LINGKUNGAN: ANTARA MANDATORY DAN VOLUNTARY - Dian Anita Nuswantara, (Pelangi Ilmu, 2008)
Abstract The choice between mandatory and voluntary disclosure on environmental reporting is still controversy. This paper tries to describe that mandatory is prefer than voluntary due to measurement problem and the urgency of environment impact.